Effectiveness of Lifestyle Modification in Late Adolescent Females with Normal BMI Polycystic Ovarian Syndrome - Snehal Walmik Hukire1, T. Poovishnu Devi2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background and Objectives: The prevalence of PCOS varies from 2.2% to 26% in different countries. Between 20-50% of women with PCOS are normal weight or lean and the pathophysiology of the disorder in these women may differ from that of obese women; It has been suggested that PCOS develops in non obese women because of a hypothalamic pituitary defect that results in increase release of LH. To determine the effectiveness of life style modification in late adolescent with normal BMI polycystic ovarian syndrome . Material and Methodology: 28 Normal BMI women with polycystic ovary syndrome were selected for the study. They received the life style modification including diet plan exercise plan. Pre –assessment of body weight is measured by body mass index (BMI),waist-hip ratio(W-H Ratio) and quality of life was scored as per polycystic ovarian syndrome questionnaire(PCOSQ) and post-interventional assessment was taken for the same after 3 months. The exclusion criteria included Type II diabetes, Cardio vascular problems, any concurrent hormone therapy within 6 weeks, pregnant women’s or who are willing to conceive. Result: Statistical analysis for PCOSQ was extremely significant (P value=0.0001).Statistical analysis for BMI revealed not significant in post intervention .Statistical analysis for W-H Ratio revealed not significant in post intervention. Conclusion: Lifestyle modification helped in maintaining weight and showed increased quality of life in women with polycystic ovarian syndrome (PCOS).